Adipose-Derived Mesenchymal Stem Cells for Treatment Tertiary Failure Diabetes Mellitus Type 2 - Purwati (Trans Tech Publications, 2017)
Recent progress in diabetes mellitus therapy has focused attention on generation of surrogate β-cells from mesenchymal stem cells (MSCs) derived adult tissues. In this study, we conducted a phase I clinical trial in patients with type 2 diabetes mellitus in various age between 30-79 years old who were treated with autologous adipose-derived MSCs transplantation. MSCs injected into diabetic patients through catheterization then we measured levels of fasting blood glucose, 2h postprandial blood glucose, insulin, c-peptide pre and post stem cell transplantation, also HbA1c. Levels of blood glucose (fasting and 2h post prandial) and insulin were absolutely decreasing after injection. Meanwhile, level of c-peptide was increasing after injection. Level of HbA1c was significantly decreasing after 3 months injection. Thus, adipose-derived mesenchymal stem cells for treatment tertiary failure diabetes mellitus type 2 was better than insulin treatment only.